A molecular movie of Interatomic Coulombic Decay in NeKr. (August 2015) - Trinter, Florian; Miteva, Tsveta; Weller, Miriam; Albrecht, Sebastian; Hartung, Alexander; Richter, Martin; Williams, Joshua; Gatton, Averell; Gaire, Bishwanath; Weber, Thorsten; Sartor, James; Landers, Allen; et al.
Synopsis: Interatomic Coulombic Decay in mixed NeKr dimers has been measured time-resolved and the nuclear dynamics of the decay have been investigated.